Membangun Karakter Siswa Hindu Berlandaskan Tri Hita Karana di Sekolah Dasar Kota Mataram Nusa Tenggara Barat - Ayu Suci, I Ratu Agung; Wijana, I Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Building the character of a nation starts from the level of education that exists in Indonesia, which can be obtained through formal, informal and non-formal education levels. Building character in children is not only done by educational institutions such as schools but can be instilled by each child's parents. Character education is a process of instilling human values in everyday life in order to become a person with noble character, morals, self-confidence, politeness, and tolerance towards other people. This research examines or analyzes building the character of Hindu students based on Tri Hita Karana. The focus of the study includes character education, Tri Hita Karana, and Hindu students. The aim of this research is to discuss the values contained in the Tri Hita Karana teachings in building the character of students in the city of Mataram, West Nusa Tenggara and the forms of their implementation in life at family, school and in society as a high-quality young generation of Hindus. The method used to examine the problems in this research uses a qualitative descriptive method and is supported by various literature related to the teachings of the Tri Hita Karana concept. The results obtained in this research are that building students' character must be taught as early as possible and the implementation of Tri HIta Karana can be done in three ways, namely the harmonious relationship between humans and God (Parhyangan), the harmonious relationship between humans and humans (pawongan), and the relationship between humans and God. natural environment (pabelasan). So that Hindu students have a character that is based on the teachings of dharma and is guided by the sacred Veda.